2020
DOI: 10.1080/00087041.2019.1660513
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Eyes: How Do Users Get Started with a Coordinated and Multiple View Geovisualization Tool?

Abstract: Maps are frequently combined with data displays in the form of coordinated and multiple views (CMV). Although CMV are valuable geovisualization tools, novice users may find them complex and thus require explanation. However, no tutorial guidelines have been developed that indicate what is helpful in understanding CMV geovisualization tools. We therefore conducted a study on the learnability of a CMV tool, informed with eye-tracking data, talk-aloud and interaction logs. We have investigated how untrained users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This assumption should be investigated in further studies. Due to the assumption that the individual AOIs are assigned different importance by the solver over time, some studies suggest a time-sequential analysis of the transitions for individual time intervals [42,53,59,61]. For example, in the present case, it is possible that AOI_Question is considered by some students, depending on their solution strategy, only at the beginning but not at the end of the task solving process.…”
Section: Rq1: How Do Correct and Incorrect Solvers Differ In Their Proportion Of Fixations On Aois Of Graph Understanding Tasks?mentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption should be investigated in further studies. Due to the assumption that the individual AOIs are assigned different importance by the solver over time, some studies suggest a time-sequential analysis of the transitions for individual time intervals [42,53,59,61]. For example, in the present case, it is possible that AOI_Question is considered by some students, depending on their solution strategy, only at the beginning but not at the end of the task solving process.…”
Section: Rq1: How Do Correct and Incorrect Solvers Differ In Their Proportion Of Fixations On Aois Of Graph Understanding Tasks?mentioning
confidence: 99%
“…Transitions are a powerful eye-tracking metric to analyze gaze shifts between, for example, different web page elements [57], distances in air traffic observation [58], use of software [59] or image-text integration of assessments [43]. Previous studies on graph understanding [23,41,44] between different groups (here, correct and incorrect solvers) showed that certain transitions occur more often for one group than for others.…”
Section: Rq1: How Do Correct and Incorrect Solvers Differ In Their Proportion Of Fixations On Aois Of Graph Understanding Tasks?mentioning
confidence: 99%
“…Moreover, previous years' eye tracking has been used as the main experimental method for the evaluation of the effectiveness of specific types of maps (e.g., [21][22][23]) or different map-based graphical user interfaces (e.g., [24]) working either on typical or smaller (i.e., smartphones) displays [25], under different types of tasks (e.g., [26,27]) and conditions. Substantial contributions have also been presented in the domains of geography map-use education [28,29] and in geovisualization tools' learnability effects [30]. Additionally, recent research studies appearing in the field deal with more theoretical concepts related to the map symbolization process as well as the effectiveness of the fundamental element of map design used either in classic static representations [31] or in modern animated maps [32].…”
Section: Current Trendsmentioning
confidence: 99%
“…This methodological approach contributed to a deeper understanding of how people perform visual interaction strategies combined with inference and decision-making in pattern recognition. However, studying visual behavior while using the maps' graphical user interface contributed to highlighting differences in visual strategies over time [30,41,42].…”
Section: Current Trendsmentioning
confidence: 99%
“…In examining the choropleth mapping of epidemiological data, Brewer and Pickle (2002: 679) suggest that facilitating a comparison between maps is more important than optimizing classification for a single map. Nevertheless, while dashboards provide coordinated and multiple views to provide situational awareness, Golebiowska et al (2020) recommend that tutorials should be offered because of their visual complexity.…”
Section: Mapping and Counter-mapping Covid-19: From Crisis To Cartocracymentioning
confidence: 99%